Preliminary analysis of “The Effectiveness of using Virtual Reality approach in Electromagnetic Theory Subject Courseware” in MTUN. - Ishak, Norshahidatul Hasana; Bakar, Norasiken (2010)
This paper is about the study of applying a virtual reality approaches on studying electromagnetic theory. It will examine the effectiveness of this approach in the field of education as some subject need high imagination to understand. This topic has cover about the surface of 3D environment and the usage plus the impact of the virtual reality approaches in this project. It also explains about the problem that has been found until the development of the courseware with virtual reality approach. This project focus for students and lecturers guideline, and will exposed them to the used of ICT and multimedia tool in learning as one of the teaching tool. Data have been collected by using questionnaire method, which four Malaysia technical universities have been chosen to prove that Electromagnetic Theory (EMT) subject is the hardest subject in engineering field as it is the fundamental subject for future engineer. At first, 16 objectives question have been given to 10% student those have took the subject before for each universities. These questions are to test their understanding about EMT subject, as before they were using traditional approach in their study. All questions are from four subtopic in the EMT subject, which are Vector calculus, Electrostatic, Magnetostatic, and Wave application. Each subtopic contains four questions. Then analysis have been done to check the most hardest subtopic so that it will be chosen as a main subtopic that will be focus on, which 3D and Virtual reality approach will be applied on it. It is believe that the effectiveness of these approaches can be seen if the method applies in the hardest part gives positives results. Not only survey on students have been done, but also to the lecturer’s and as a same method, 10 % of survey from lecturers that teach EMT subject in all Malaysia Technical Universities have been taken, and analysis have been done, as a result most lecturers agreed if 3D and Virtual reality approaches applied in studying the subject to make students easily understand about the subject as this subject need high imagination. This paper presents a summary of the experimental assessment process and findings regarding the educational value of the multimedia courseware with three dimensional and virtual reality approaches applied.